RETRACTED: THE RELATIONSHIP OF ACADEMIC BURNOUT AND INTERNET ADDICTION IN ACADEMIC ACHIEVEMENT: THE MEDIATING ROLE OF OPTIMISM IN STUDENTS - Novian Candra Kurniawan; Khusnul Khotimah; Zerina Nurkhamamah; Novian Candra Kurniawan; Khusnul Khotimah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This article was retracted at the author's request because it was submitted to two journals. The document and its content has been removed from Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, and reasonable effort should be made to remove all references to this article.